Morphometric characteristics of indigenous chicken in rural communities of southern Ecuador - Villacís Rivas, Gustavo (2016)
The present study aimed to study the morphological variability of indigenous chicken in the south of Ecuador. A total of 200 adult individuals (31 males and 169 females) were characterized with the support of 14 descriptors for morphometric characterization established by FAO. On these measurements, body weight and length of the tarsus were selected due to their direct relationship with the productive characteristics of interest to the study. Ten biotypes of indigenous chicken were identified having evident physical differences among them. By using a multivariate statistical analysis, the biotypes were grouped in three clusters for females and in two clusters for males.